Faktor-Faktor Determinan Penyebab Kejadian Stunting dilihat dari Faktor Ibu di Wilayah Kerja Puskesmas Mondokan Kabupaten Sragen - Putri Erna Arselia Noviana; Anjar Nurrohmah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Stunting is one of the causes of death and a contributing factor to the number of children exposed to disease, 3.1 million or 45% of the causes of death in the world besides disability. Many factors are associated with the incidence of stunting in toddlers, one of which is factors seen from mothers such as upper arm circumference, education, age at pregnancy and income. The prevalence of stunting in the working area of public health center of mondokan sragen regency was 417 cases in December 2023. Objective: Knowing the determinant factors causingof the incidence of stunting seen from maternal factors in the working area of public health Center of Mondokan Sragen Regency. Methods: The study used descriptive methods, sampling using quota sampling techniques, 81 respondents, the instrument used used a checklist sheet containing the characteristics of stunting factors. Results: the results showed that the majority of the characteristics of upper arm circumference <23.5 cm (58%), the latest elementary school education (59.1%), maternal age during pregnancy 20-35 years (85.2%), income <2,049,000 (71.6%). Conclusion: the determinant factors in the working area of Puskesmas Mondokan are upper arm circumference, education, maternal age at pregnancy, income,